PENGGUNAAN MEDIA TIMBANGAN BILANGAN UNTUK MENINGKATKAN KEMAMPUAN MENJUMLAHKAN BAGI ANAK TUNAGRAHITA RINGAN - Wita Maya Sari (Jurnal Penelitian Pendidikan Khusus, 2013)
The research is motivated from problems seen in the field, namely children mild mental retardation X class II discourse capable of summing the number to 5, while the class II special school curriculum requires that children are able to add up the number to 10. This is evident from the ability to start working on a number of children in the given problem. Thus the researcher seeks help to improve a child's ability mild mental retardation in the sum number via Media Scales Numbers. Scales Numbers is a tool designed to help children in solving addition problems by hanging small blocks on the left and right scales that scales into equilibrium.The research methodology used is a single-subject research (SSR) with the research design is AB, which is the sum of numbers compare the ability of mild mental retardation in the child's baseline condition and treatment condition. Data analysis techniques are used based on the observation data in the form of Visual Analysis Of Graph.The results were analyzed included the number of observations at seven times the baseline condition and treatment condition nine times. The results of this study aimed at the analysis of the data in the conditions and data analysis between conditions indicating a change in the child's ability to sum number X into a better direction. From the results of this data acquisition can be concluded that the media Scales Numbers can be used to improve the sum of the child class II mild mental retardation. Suggested for classroom teachers or teachers of mathematics in order to use Numbers Scales for children in learning math mild mental retardation.